Acoustical properties of porous layer – undeformable halfspace system at normal incidence of harmonic wave - CIESZKO, M. (Archives of Acoustics, 1992)
The acoustical properties of a system composed of a porous layer and an undeformable solid halfspace, immersed in a barotropic fluid, are analyzed for the case of normal incidence of a harmonic wave. The explicit forms of expressions of the wave absorption coefficients were obtained for different particular configurations of the system. This allowed us to discuss the dependence of the absorption coefficient on the dissipative properties of a fluid and on the parameters characterizing the pore structure of a porous layer, in a wide range of frequencies of the incident wave. It was shown that the dissipative properties of the fluid do not considerably change the value of resonance frequencies. However, these properties as well as the parameters of the skeleton pore structure strongly influence the coefficient of wave absorption.